Chronic kidney disease among adult participants of the ELSA-Brasil cohort: association with race and socioeconomic position. Issue 4 (28th October 2015) - Barreto, Sandhi M; Ladeira, Roberto M; Duncan, Bruce B; Schmidt, Maria Ines; Lopes, Antonio A; Benseñor, Isabela M; Chor, Dora; Griep, Rosane H; Vidigal, Pedro G; Ribeiro, Antonio L; Lotufo, Paulo A; Mill, José Geraldo
Abstract : Background: There is increased interest in understanding why chronic kidney disease (CKD) rates vary across races and socioeconomic groups. We investigated the distribution of estimated glomerular filtration rate (eGFR), urinary albumin–creatinine ratio (ACR) and CKD according to these factors in Brazilian adults. Methods: Using baseline data (2008–2010) of 14 636 public sector employees (35–74 years) enrolled in the Brazilian Longitudinal Study of Adult Health (ELSA)-Brasil multicentre cohort, we estimated the prevalence of CKD by sex, age, race and socioeconomic factors. CKD was defined as ACR≥30 mg/g and/or eGFR<60 mL/min/1.73 m 2 . GFR was estimated by CKD epidemiology collaboration without correction for race. We used logistic regression to estimate the association of race and socioeconomic position (education, income, social class and occupational nature) with CKD after adjusting for sex, age and several health-related factors. Results: The prevalence of high ACR or low eGFR, in isolation and combined, increased with age, and was higher in individuals with lower socioeconomic position and among black individuals and indigenous individuals. The overall prevalence of CKD was 8.9%. After full adjustments, it was similar in men and women (OR=0.90; 95% CI 0.79 to 1.02) and increased with age (OR=1.07; 95% CI 1.06 to 1.08). Compared to white individuals, black individuals (OR=1.23; 95% CI 1.03 to 1.47), 'pardos' (OR=1.16; 95% CI 1.00 to 1.35) and Indigenous (OR=1.72; 95% CI 1.07 to 2.76) people had higher odds for CKD. Having high school (OR=1.15; 95% CI 1.00 to 1.34) or elementary education (OR=1.23; 95% CI 1.03 to 1.47) increased the odds for CKD compared to those having a university degree. Conclusions: There were marked discrepancies in the increases in reduced eGFR and high ACR with age and race. The higher prevalences of CKD in individuals with lower educational status and in non-whites were not explained by differences in health-related factors.